Implementation of the SIGPUKAN Website in Providing Statistical Data on The Processing and Marketing of Fishery Products in East Java - Chindy Via Rosita; Vidya Imanuari Pertiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Indonesia, as a maritime country, holds significant potential in the marine and fisheries sector, with East Java being one of the provinces that contributes substantially to investment in this sector. To support investment development, the East Java Marine and Fisheries Agency has developed the Geographic Information System for Fisheries Entrepreneurs (SIGPUKAN), a digital platform that provides statistical data on the processing and marketing of fishery products. This study aims to analyze the implementation of SIGPUKAN in providing statistical data using Edward III's implementation theory. The research method employed is qualitative with a case study approach through observation and interviews. The results indicate that the implementation of SIGPUKAN has been effective, as evidenced by the regular updating of statistical data, ensuring its relevance to the administrative needs of the agency and the general public. Additionally, the platform’s mapping feature for marine and fisheries potential assists investors in identifying precise investment locations. This innovation promotes data transparency and enhances the efficiency of public services. The implementation of SIGPUKAN is expected to strengthen collaboration between the government, entrepreneurs, and the public in providing statistical data that supports the development of the marine and fisheries sector in East Java.